2010
DOI: 10.1158/1055-9965.epi-09-1213
|View full text |Cite
|
Sign up to set email alerts
|

Grade-Specific Expression of Insulin-like Growth Factor–Binding Proteins-2, -3, and -5 in Astrocytomas: IGFBP-3 Emerges as a Strong Predictor of Survival in Patients with Newly Diagnosed Glioblastoma

Abstract: Background: Insulin-like growth factor (IGF)-binding protein (IGFBP) isoforms have been implicated in the pathogenesis of human neoplasms including glioma. In view of this, we evaluated the expression of IGFBP isoforms (IGFBP-2, -3, and -5) during malignant progression of astrocytoma and their prognostic significance in glioblastoma.Methods: The expression of IGFBP isoforms was analyzed in diffusely infiltrating astrocytomas by realtime quantitative PCR (n = 203) and immunohistochemistry (n = 256). Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 35 publications
5
86
0
Order By: Relevance
“…Enhanced activation of NF-κB signaling pathway in glioblastoma cells (Wang et al, 2004) may also be involved in the upregulation of IGFBP-2 transcription (Cazals et al, 1999). The prognostic impact of IGFBPs expression in patients with newly diagnosed glioblastoma was recently reported (Santosh et al, 2010), with protein expression of IGFBP2, IGFBP 3 and IGFBP5 being significantly associated with shorter survival by univariate Cox regression analysis. However, multivariate Cox proportional hazards model showed that only IGFBP3 had independent prognostic impact.…”
Section: Expression Of Igfbp2 In Gliomas and Its Correlation With Hismentioning
confidence: 98%
“…Enhanced activation of NF-κB signaling pathway in glioblastoma cells (Wang et al, 2004) may also be involved in the upregulation of IGFBP-2 transcription (Cazals et al, 1999). The prognostic impact of IGFBPs expression in patients with newly diagnosed glioblastoma was recently reported (Santosh et al, 2010), with protein expression of IGFBP2, IGFBP 3 and IGFBP5 being significantly associated with shorter survival by univariate Cox regression analysis. However, multivariate Cox proportional hazards model showed that only IGFBP3 had independent prognostic impact.…”
Section: Expression Of Igfbp2 In Gliomas and Its Correlation With Hismentioning
confidence: 98%
“…High expression levels of the IGFBP-3 gene were associated with unfavorable prognostic characteristics in breast cancer (32). Santosh et al (33) reported that IGFBP-3 overexpression in tumor tissues was an independent predictor of reduced survival rate in patients with newly diagnosed glioblastoma. By contrast, Aishima et al (34) identified that high expression levels of IGFBP-3 were independently associated with an improved survival rate in patients with hepatocellular carcinoma.…”
Section: Univariate Analysismentioning
confidence: 99%
“…Genetic heterogeneity in GBM has been proposed to explain the limitations in the effectiveness of current therapies, which necessitates the need for prognostic gene signature (2). Many genetic and epigenetic alterations as well as expression of some genes have been correlated with poor or better prognosis (3)(4)(5)(6)(7). In addition, molecular biomarkers like methyl guanine methyl transferase (MGMT) promoter methylation, isocitrate dehydrogenase 1 (IDH1) mutation status, and Glioma-CpG Island Methylator Phenotype (G-CIMP) have been identified as GBM prognostic indicators (1,8,9).…”
Section: Introductionmentioning
confidence: 99%